2019
DOI: 10.1111/1440-1703.12003
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Eucalyptus plantations affect small mammal ectoparasites abundance but not individual body condition

Abstract: Biodiversity is recognizably affected by land conversion for agriculture. However, the assessment of impacts on wildlife often lacks information on populations structure and individuals' condition, allowing only a limited view of the problem. Individual body condition/health can influence animal's reproductive success or survival. Eucalyptus globulus plantations are important forestry systems in Iberia, being the widest forested‐land use in Portugal, which hosts the broadest European E. globulus coverage. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
5
1
Order By: Relevance
“…As predicted by epidemiological models, a high host density increases the likelihood of parasite infection [58,59]. Although there were fewer A. agrarius individuals in the Camellia forest than the flood-meadow, the ectoparasite load was greater in the Camellia forest, possibly due to habitat anthropogenizationt, which is known to promote the presence and density of parasites [30,60]. Notably, during the rainy season, the floodmeadow is submerged, and small mammals such as A. agrarius will migrate to surrounding habitats.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As predicted by epidemiological models, a high host density increases the likelihood of parasite infection [58,59]. Although there were fewer A. agrarius individuals in the Camellia forest than the flood-meadow, the ectoparasite load was greater in the Camellia forest, possibly due to habitat anthropogenizationt, which is known to promote the presence and density of parasites [30,60]. Notably, during the rainy season, the floodmeadow is submerged, and small mammals such as A. agrarius will migrate to surrounding habitats.…”
Section: Discussionmentioning
confidence: 89%
“…Our study assessed the effect of an oil tea plantation on small mammals at three levels: (1) community level, evaluating diversity, and composition; (2) population level, assessing density, and sex ratio; and (3) individual level, examining body condition index, and ectoparasite load. As oil tea plantations are a monoculture in our study area, we predict that the conversion of natural habitats to Camellia forests could result in low community diversity and population density because of the absence of habitat diversity and complexity [29], and poor body condition due to ecosystems simplification and anthropic disturbance [24,30]. Our findings hold significant implications for riparian vegetation restoration and management, given the critical role of small mammals in ecosystems.…”
Section: Introductionmentioning
confidence: 80%
“…In general, the prevalence of ectoparasites on rodents in disturbed areas (e.g., in cities and agricultural lands) has been reported to range between 23% and 89% (Baak‐Baak et al., 2018; Hamidi et al., 2015; Herrero‐Cófreces et al., 2021; Moravvej et al., 2016; Teixeira et al., 2019), while in undisturbed areas (e.g., protected areas) this ranges between 57% and 98% (Bohn et al., 2017; Fantozzi et al., 2022; Kiffner et al., 2011; Thanee et al., 2009). Several studies have compared ectoparasite prevalence between disturbed and undisturbed sites in the same areas (Durden et al., 2004; Kiene et al., 2020; Smith et al., 2021; Veloso‐Frías et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that Eucalyptus exotic plantations impose varying taxa and landscape-specific impacts on native wildlife (e.g., changes in activity and occupancy patterns, modification of interspecific relationships, and increase in parasites' prevalence; [9][10][11][12]), leading to changes in communities' composition (e.g., simplification of predator communities; [13]), thus inducing conservation concerns (e.g., [14,15]). This forestry system management affects the diversity and abundance of native understory [7], which is one of the most influential factors supporting biodiversity in forestry plantations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large cover of Eucalyptus plantations in Europe (covering almost 1.5 million ha; [25]), few studies have assessed how these landscapes affect wildlife health/fitness (i.e., body condition), particularly in small mammals, whose condition will affect upper trophic levels within the community, e.g., [26]. Additionally, the available data are from local-scale studies (e.g., only one study area), and often did not present conclusive results regarding the effect of plantations on small mammals' body condition [12,17]. Small mammals are responsible for some fundamental ecosystem functions such as soil aeration and seed dispersal [27].…”
Section: Introductionmentioning
confidence: 99%